Atlas of Lung Pathology (Atlas of Anatomic Pathology,, 2018)
This book provides pathologists-in-training as well as experienced practitioners an easy-to-use practical diagnostic guide for lesions involving the lung and pleura. It also serves as a reliable resource for clinicians interested in the histopathologic features that define the entities that afflict their patients. This text covers a breadth of common problems likely to cross your microscope but without a level of detail likely to satisfy a desire for deep knowledge of their biology. The fourteen chapters begin with a brief overview of normal histology before moving on to incidental findings, followed by non-neoplastic and finally neoplastic diseases. Individual diseases include a brief introduction followed by gross photographs for selected entities and multiple photomicrographs at different magnifications with detailed legends describing the findings. The introductory narratives are intentionally concise, including only essential clinical and radiological information and key pathologic features. The emphasis in this book is on the histologic diagnosis of diseases using routinely stained slides as the foundation with a focus on high-quality hematoxylin-eosin-stained sections. Gross illustrations are included for those entities in which gross examination may play an important role in diagnosis. Illustrations of immunohistochemical stains are limited to those that are diagnostically relevant and/or necessary for certain tumor categories. The Atlas of Lung Pathology provides a useful resource for pathologists and practitioners at every level of experience in evaluating lung and pleural diseases likely to be encountered in any busy pathology practice. .